Weaknesses in European e-Waste Management - Sangeeta Mohanty; Elise Vermeersch; Juha Hintsa; Vittoria Luda Di Cortemiglia; Mary Liddane (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
Illegal exports of waste electrical and electronic equipment -WEEE - from industrial to developing countries is a growing criminal phenomena posing serious threats to the human health and the environment. Several loopholes in the current jurisdictional systems along the supply chain in the European Union; deficiencies in law enforcement capacity, knowledge and training; and other supply chain related weaknesses prevent an effective response to such criminal activity. This paper identifies the vulnerabilities along the supply chain, the shortcomings in the legislative framework around WEEE, and its limited implementation and enforcement that facilitate leakages from the legal WEEE streams. An understanding of the weaknesses will enable the governmental bodies to develop appropriate counter-measures to improve the prevention, detection, investigation and prosecution of WEEE violations. This paper presents a comprehensive gap analysis across the EU member states, Norway and Switzerland. It focuses on the key issues surrounding the international and national legislative frameworks and the implementation thereof, law enforcement capacity, knowledge and training, information management, and penalties and prosecution. The study helps to identify the underlying problems and the key concerns faced by national authorities - and, this information will lead to a set of recommendations for the European Commission and the EU member states to address the problem of illegal e-waste exports.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; WEEE Supply Chain; Illicit Trade; Supply Chain Security; FP7-CWIT